Servant mage - Elliott, Kate, 1958- (Tordotcom, 2022)
"In Kate Elliott's Servant Mage, a lowly fire mage finds herself entangled in an empire-spanning conspiracy on her way to discovering her true power. They choose their laws to secure their power. Fellion is a Lamplighter, able to provide illumination through magic. A group of rebel Monarchists free her from indentured servitude and take her on a journey to rescue trapped compatriots from an underground complex of mines. Along the way they get caught up in a conspiracy to kill the latest royal child and wipe out the Monarchist movement for good. But Fellion has more than just her Lamplighting skills up her sleeve..."--